Students’ Perceptions of Difficulties in Reading English Texts among Fourth Semester Students of English Education at Islamic University of Riau - Fadila Sofi Kurnia (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Reading is an important part of language learning, but many students who learn English as a Foreign Language (EFL) still experience difficulties in understanding reading English texts. This study aims to explore the perceptions of fourth-semester students of the English Education Department at Islamic University of Riau regarding their reading difficulties. This research used a qualitative phenomenological approach. Data were collected from 20 participants through a structured questionnaire. The findings show that students face several challenges in reading comprehension, including limited vocabulary, difficulties in understanding grammar, ineffective use of reading strategies, low motivation, and problems identifying main ideas in long sentences. These findings suggest the importance of implementing appropriate teaching strategies to improve students’ reading comprehension and support their academic achievement.